Central Bank Policies and Financial Markets: Lessons from the Euro Crisis - Ashoka Mody; Milan Nedeljkovic (Center for Economic Studies and ifo Institute (CESifo), 2018)
The European Central Bank (ECB) took many measures to combat the eurozone's rolling financial crisis. For providing desperately scarce dollars to eurozone banks, the ECB relied on the U.S. Federal Reserve. Using a novel econometric framework, we identify financial markets' response to the ECB's liquidity injections and its more pro-active monetary stimulus between October 2009 and September 2012, the most intense phase of the eurozone crisis. Dollar liquidity clearly reduced stress in bond markets and improved economic sentiment, as reflected in higher equity prices. In contrast, passive euro liquidity provision and even active measures (policy rate reductions and bond market interventions) delivered modest results. Although government bond spreads did typically decline, markets remained worried that spreads could rise quickly; moreover, broad economic sentiment remained unchanged. Only the Outright Monetary Transactions (OMT) “bazooka” had a substantial beneficial effect. Overall, the results point to the ECB's limits in helping improve financial market's sentiment.
Keywords: E44; E58; C32; C38; 330; monetary policy; euro crises; uncertainty; conditional quantiles; MCMC; FAVAR